A Diagnostic Approach to Fungal Pneumonia - Azar, Marwan.M. (CHEST, 2023)

Pneumocystis jiroveci in solid organ transplantation: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Fishman, Jay A.; Gans, Hayley; Practice, the AST Infectious Diseases Community of (Clinical Transplantation, 2019)
These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of Pneumocystis jiroveci fungal infection transplant recipients. Pneumonia (PJP) may develop via airborne transmission or reactivation of prior infection. Nosocomial clusters of infection have been described among transplant recipients. PJP should not occur during prophylaxis with trimethoprim-sulfamethoxazole (TMP-SMX). Without prophylaxis, PJP risk is greatest in the first 6 months after organ transplantation but may develop later. Risk factors include low lymphocyte counts, cytomegalovirus infection (CMV), hypogammaglobulinemia, treated graft rejection or corticosteroids, and advancing patient age (>65). Presentation typically includes fever, dyspnea with hypoxemia, and cough. Chest radiographic patterns generally reveal diffuse interstitial processes best seen by CT scans. Patients generally have PO2 < 60 mm Hg, elevated serum lactic dehydrogenase (LDH), and elevated serum (1 → 3) β-d-glucan assay. Specific diagnosis uses respiratory specimens with direct immunofluorescent staining; invasive procedures may be required. Quantitative PCR is a useful adjunct to diagnosis. TMP-SMX is the drug of choice for therapy; drug allergy should be documented before resorting to alternative therapies. Adjunctive corticosteroids may be useful early. Routine PJP prophylaxis is recommended for at least 6-12 months post–transplant, preferably with TMP-SMX.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ctr.13587
Keywords: antimicrobial; corticosteroid therapy; fungal; infection and infectious agents; pneumocystis jirovecii; pneumocystis pneumonia